2001
DOI: 10.1164/ajrccm.164.5.9910103
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Corticosteroids, Combined with Long-acting β2-Agonists, Improve the Perception of Bronchoconstriction in Asthma

Abstract: The relationship between asthma medication and the perception of asthma symptoms is of interest for daily practice. Poor perception of asthma symptoms might influence patients' health care behavior and subsequently might lead to undertreatment and deterioration of their disease. This study investigated the influence of the chronic use of short-acting and long-acting beta(2)-agonists, compared with the additional use of inhaled corticosteroids on the perception of histamine-induced bronchoconstriction. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…Recently, in a subgroup of the present study population [14], the authors showed that the additional use of inhaled corticosteroids resulted in an improvement in the perception of bronchoconstriction in patients using long-acting b 2 -agonists but not in patients using short-acting b 2 -agonists. This difference might be related to the increase in BHR in the group using short-acting b 2 -agonists, resulting in greater airflow inflammation and perhaps a reduction in perception.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Recently, in a subgroup of the present study population [14], the authors showed that the additional use of inhaled corticosteroids resulted in an improvement in the perception of bronchoconstriction in patients using long-acting b 2 -agonists but not in patients using short-acting b 2 -agonists. This difference might be related to the increase in BHR in the group using short-acting b 2 -agonists, resulting in greater airflow inflammation and perhaps a reduction in perception.…”
Section: Discussionmentioning
confidence: 66%
“…Initially, patients (aged 16-60 yrs) were selected by their general practitioner (GP) if they had a history of bronchial symptoms or a clinical diagnosis of asthma [13,14]. Eligible patients then visited the lung function laboratory for an inclusion assessment.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirm the findings of Roisman et al (95) that patients treated with inhaled corticosteroids had an increased perception of symptoms than cortocosteroid-naive patients for a given degree of eosinophil inflammation. Bijl-Hofland et al (117) showed that compared with long-acting b 2 -agonists used alone, a combination of long-acting b 2 -agonists and inhaled corticosteroids had a positive effect on the perception of bronchial obstruction. A longitudinal Australian study (118) with administration of high doses of inhaled corticosteroids (budesonide) failed to show any difference between naive or previously treated patients, in terms of variation in the Borg score during the reduction of FEV 1 induced by challenge tests.…”
Section: Impact Of Anti-inflammatory Treatment On Dyspnoea In Asthmaticsmentioning
confidence: 99%
“…Inhaled corticosteroids have recently been demonstrated to heighten the sensation of dyspnoea in asthma [27,28]. Earlier research suggests theophylline (a higher centre and muscle stimulant) may increase perception of asthma [29].…”
mentioning
confidence: 99%